Antifibrotic Activity of Acylated and Unacylated Ghrelin - Elia Angelino; Simone Reano; Michele Ferrara; Emanuela Agosti; Andrea Graziani; Nicoletta Filigheddu (International Journal of Endocrinology)
Fibrosis can affect almost all tissues and organs, it often represents the terminal stage of chronic diseases, and it is regarded as a major health issue for which efficient therapies are needed. Tissue injury, by inducing necrosis/apoptosis, triggers inflammatory response that, in turn, promotes fibroblast activation and pathological deposition of extracellular matrix. Acylated and unacylated ghrelin are the main products of the ghrelin gene. The acylated form, through its receptor GHSR-1a, stimulates appetite and growth hormone (GH) release. Although unacylated ghrelin does not bind or activate GHSR-1a, it shares with the acylated form several biological activities. Ghrelin peptides exhibit anti-inflammatory, antioxidative, and antiapoptotic activities, suggesting that they might represent an efficient approach to prevent or reduce fibrosis. The aim of this review is to summarize the available evidence regarding the effects of acylated and unacylated ghrelin on different pathologies and experimental models in which fibrosis is a predominant characteristic.